Predisposing Factors for Chemotherapy-induced Nephrotoxicity in Patients with Advanced Esophageal Cancer Who Received Combination Chemotherapy with Docetaxel, Cisplatin, and 5-fluorouracil - Mohri, Junichi (J Transl Int Med, 2018)
BACKGROUND AND OBJECTIVES: We retrospectively studied the predisposing factors for nephrotoxicity in the patients with advanced esophageal squamous-cell carcinoma who received combination chemotherapy with docetaxel, cisplatin, and 5-fluorouracil (DCF therapy). METHODS: Between January 2010 and March 2014, 41 patients with Stage IB to III esophageal squamous-cell carcinoma received the DCF therapy (docetaxel 70-75 mg/m(2), day 1; cisplatin 70-75 mg/m(2), day 1; 5-fluorouracil 750 mg/m(2), days 1-5) in our hospital. Renal dysfunction was defined as a creatinine clearance (Ccr) of less than 60 mL/min. Predictors of nephrotoxicity were identified through logistic-regression analysis. RESULTS: Nephrotoxicity developed in 20 patients and did not develop in 21 patients. Nephrotoxicity developed during the first course of DCF therapy in 16 patients, the second course in 3 patients, and the third course in 1 patient. The dose of DCF therapy was decreased in 8 patients with nephrotoxicity and 7 patients without nephrotoxicity. Multivariate analysis showed that a low Ccr level immediately before DCF therapy was an independent risk factor for the development of nephrotoxicity (odds ratio, 0.932; 95% confidence interval, 0.876 to 0.992; P = 0.027). On receiver operating characteristic curve analysis, the optimal cutoff value of Ccr for the development of nephrotoxicity was 75.8 mL/min. The 2-year overall survival rate was 84.2% in patients with nephrotoxicity and 90.0% in patients without nephrotoxicity (P = 0.635). CONCLUSIONS: Low Ccr levels immediately before DCF therapy are a risk factor for the development of nephrotoxicity. Patients should therefore be carefully monitored.